Preparation method and application of vertically-oriented boron nitride / epoxy resin heat-conducting composite material under magnetic field

Through the method of high-pressure homogenizer processing and magnetic field orientation, a highly efficient thermally conductive vertically oriented boron nitride/epoxy resin thermal conductive composite material under a magnetic field is prepared, which solves the problem of high cost, complex process and application scope of the filler directional arrangement method in the existing technology. Narrow problem, achieving efficient heat dissipation effect of electronic components.

CN119331381AActive Publication Date: 2025-01-21ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD

Patent Information

Application Number
CN202411444881.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing filler orientation arrangement methods are costly, complex in process and narrow in application range, and cannot meet the efficient heat dissipation needs in the field of advanced electronic components.

Method used

Through the cyclic flushing of a high-pressure homogenizer, boron nitride is induced to peel off and physically bond with ferroferric oxide to prepare magnetically functionalized boron nitride nanosheet fillers, and use a magnetic field to achieve vertical orientation of boron nitride nanosheets. Vertically oriented boron nitride/epoxy resin thermal conductive composite materials were prepared under magnetic field.

Benefits of technology

The high-efficiency thermal conductivity of epoxy resin has been improved, with the thermal conductivity reaching 1.81W/(m·K), which is 9.05 times that of pure epoxy resin. At the same time, the process is simple, high efficiency, wide range of applications, and suitable for electronic packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331381A_ABST
    Figure CN119331381A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a vertically-oriented boron nitride / epoxy resin heat-conducting composite material under a magnetic field, and belongs to the field of composite materials. The invention aims to solve the problems of high cost, complex process and narrow application range of the existing filler directional arrangement method. The method comprises the following steps: 1, preparing a mixed solution of boron nitride and ferroferric oxide; 2, preparing a boron nitride nanosheet solution with ferroferric oxide attached to the surface; (3) preparing BNNS coated Fe3O4; and 4, preparing the vertically-oriented boron nitride / epoxy resin heat-conducting composite material under the magnetic field. The invention relates to application of a vertically-oriented boron nitride / epoxy resin heat-conducting composite material in electronic packaging under a magnetic field. The heat conductivity of the epoxy resin can be effectively improved, the process is simple and reliable, the efficiency is high, the cost is low, the heat conductivity coefficient is high, and the method can be applied to electronic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a preparation method and application of a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field. Background Art

[0002] With the rapid development of electronic components towards high-density integration and miniaturization, the power density of electronic devices continues to rise, and the accumulated heat generated during operation has become a major challenge affecting the reliability and efficiency of components. In high-power application scenarios, such as fast charging of electric vehicles and mobile phones, thermal runaway of batteries or chips has become the main cause of safety accidents. According to statistics, when the operating temperature increases by 2°C, the long-term stability of electronic equipment will decrease by 10% and the service life will decrease by 2 times. Therefore, in order to quickly conduct the heat accumulated in the components, packaging materials with efficient heat dissipation capabilities are urgently needed.

[0003] Epoxy resins are widely used in the field of electronic packaging due to their advantages such as low cost, good processability and high insulation. However, most epoxy resins have low intrinsic thermal conductivity (≤0.5W / (m·K)), which cannot meet the heat dissipation requirements of advanced thermal management systems. A large number of studies have shown that boron nitride nanosheets (BNNS) have unique advantages in enhancing the thermal conductivity of epoxy resins. BNNS has extremely high thermal conductivity in the in-plane direction (theoretically 1700–2000W / (m·K)) due to its two-dimensional sheet-like high aspect ratio structural characteristics, but its cross-plane thermal conductivity is only 30W / (m·K). In order to take advantage of the high in-plane thermal conductivity of BNNS, it is crucial to accurately control the microstructure arrangement of inorganic fillers. Several methods have been used to achieve directional arrangement of BNNS, including blade coating, ice template method and hot pressing method, but these methods are either costly and have complex process requirements, or are too narrow in scope and not universal. For example, Chinese patent 202310234646.5 obtains a multilayer solid film by multiple scraping and casting, and cuts the cross section to obtain a vertically arranged boron nitride gasket, but each scraping needs to wait for curing time. This method is complex and inefficient, and can only be used for thermoplastic materials. Therefore, it is urgent to develop a filler directional arrangement method with simple process, high efficiency and wide application range to meet the heat dissipation needs in the field of advanced electronic components. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of high cost, complex process and narrow application range of the existing filler oriented arrangement method, and to provide a preparation method and application of a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field.

[0005] The present invention utilizes the cyclic flushing of a high-pressure homogenizer to induce the exfoliation of boron nitride and physical bonding with ferroferric oxide by multiple fluid dynamics modes such as shearing, cavitation and impact, and efficiently prepares magnetically functionalized boron nitride nanosheet fillers. Then, the vertical orientation of the boron nitride nanosheets is achieved through the action of a magnetic field. The thermal conductivity of the prepared composite material is 1.81 W / (m·K), thereby achieving the purpose of enhancing the thermal conductivity of epoxy resin and being used for electronic packaging applications.

[0006] A method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field is specifically completed by the following steps:

[0007] 1. Preparation of a mixed solution of boron nitride and ferroferric oxide:

[0008] Adding boron nitride and ferroferric oxide into isopropanol, and dispersing them evenly under ultrasonic conditions to obtain a mixed solution of boron nitride and ferroferric oxide;

[0009] 2. Using a high-pressure homogenizer to treat a mixed solution of boron nitride and ferroferric oxide for a period of time to obtain a boron nitride nanosheet solution with ferroferric oxide attached to the surface;

[0010] 3. The boron nitride nanosheet solution with ferroferric oxide attached to the surface is vacuum filtered, the obtained solid matter is washed, and then isopropanol is added, and the supernatant is collected after centrifugation for a period of time, and the collected supernatant is vacuum dried to obtain BNNS@Fe3O4;

[0011] 4. BNNS@Fe3O4, epoxy resin, curing agent and accelerator are vacuum stirred for a period of time to mix evenly to obtain a mixed colloid; the mixed colloid is transferred to a polytetrafluoroethylene disc mold, the mold containing the mixed colloid is placed between two electromagnets, and the temperature is increased and cured under a magnetic field to obtain a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field.

[0012] Application of a vertically oriented boron nitride / epoxy resin thermal conductive composite material in electronic packaging under a magnetic field.

[0013] Compared with the prior art, the present invention has the following significant effects:

[0014] (1) The present invention provides a method for preparing a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field. The method can realize vertical oriented arrangement of fillers in epoxy resin, and can make full use of the high in-plane thermal conductivity of boron nitride; the method can construct a vertical chain-like thermal conductive path, thereby improving the out-of-plane thermal conductivity of the polymer matrix; the thermal conductivity of the vertically oriented boron nitride / epoxy resin thermal conductive composite material (BNNS@Fe3O4 / EP composite material) under a magnetic field prepared by the present invention reaches 1.81W / (m·K), which is 9.05 times that of pure epoxy resin (0.2W / (m·K)); at the same time, the magnetic-assisted high orientation method can be adapted to the current industrial epoxy resin preparation process, can be formed synchronously with the substrate, and can meet the requirements of various shapes and sizes, and has the universality of industrial preparation;

[0015] (2) The present invention uses a high-pressure homogenizer to perform functional treatment on boron nitride. The liquid phase flushing of the high-pressure homogenizer can simultaneously realize the stripping and magnetic functionalization of boron nitride. Compared with liquid phase ultrasonic stripping and hydrothermal magnetization, this method has high stripping efficiency, simple and stable process and can be prepared on a large scale industrially;

[0016] (3) The present invention avoids the use of harsh chemicals and high energy consumption procedures. The auxiliary solvent isopropyl alcohol in the magnetic stripping process is green and safe, does not involve dangerous goods, and has the characteristics of sustainable development. The isopropyl alcohol used as the auxiliary solvent for magnetic stripping can be reused many times and is recyclable.

[0017] (4) The boron nitride / epoxy resin thermal conductive composite material vertically oriented under a magnetic field used in the present invention has a high thermal conductivity and can be applied to electronic packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a picture of the BNNS@Fe3O4 powder prepared in Example 1 dispersed in isopropanol and attracted by a permanent magnet;

[0019] Figure 2 This is the SEM image of BNNS@Fe3O4 prepared in Example 1;

[0020] Figure 3 This is a SEM image of a cross section of a vertically oriented boron nitride / epoxy resin thermally conductive composite material prepared in Example 1 under a magnetic field;

[0021] Figure 4 It is a comparison diagram of XRD of the vertically oriented boron nitride / epoxy resin thermal conductive composite material prepared under a magnetic field in Example 1 and the boron nitride / epoxy resin thermal conductive composite material prepared without using a magnetic field;

[0022] Figure 5This is a comparison chart of the thermal conductivity of the vertically oriented boron nitride / epoxy resin thermally conductive composite materials prepared in Examples 1-4 under a magnetic field and the boron nitride / epoxy resin thermally conductive composite materials prepared without a magnetic field. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0025] Specific implementation method 1: This implementation method is a method for preparing a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field, which is specifically completed by the following steps:

[0026] 1. Preparation of a mixed solution of boron nitride and ferroferric oxide:

[0027] Adding boron nitride and ferroferric oxide into isopropanol, and dispersing them evenly under ultrasonic conditions to obtain a mixed solution of boron nitride and ferroferric oxide;

[0028] 2. Using a high-pressure homogenizer to treat a mixed solution of boron nitride and ferroferric oxide for a period of time to obtain a boron nitride nanosheet solution with ferroferric oxide attached to the surface;

[0029] 3. The boron nitride nanosheet solution with ferroferric oxide attached to the surface is vacuum filtered, the obtained solid matter is washed, and then isopropanol is added, and the supernatant is collected after centrifugation for a period of time, and the collected supernatant is vacuum dried to obtain BNNS@Fe3O4;

[0030] 4. BNNS@Fe3O4, epoxy resin, curing agent and accelerator are vacuum stirred for a period of time to mix evenly to obtain a mixed colloid; the mixed colloid is transferred to a polytetrafluoroethylene disc mold, the mold containing the mixed colloid is placed between two electromagnets, and the temperature is increased and cured under a magnetic field to obtain a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field.

[0031] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the particle size of the boron nitride in step 1 is 10 μm to 30 μm, and the particle size of the ferrosoferric oxide is 20 nm to 100 nm. The other steps are the same as those in specific implementation method 1.

[0032] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the mass ratio of boron nitride to ferroferric oxide in step 1 is 5:(0.25-1); the concentration of boron nitride in the mixed solution of boron nitride and ferroferric oxide in step 1 is 10 mg / mL. The other steps are the same as those in specific embodiment 1 or 2.

[0033] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the pressure of the high-pressure homogenizer in step 2 is 50 MPa to 180 MPa, the number of cycles is 10 to 30 times, and the working rate is 5 L / h to 10 L / h. The other steps are the same as those of specific embodiments 1 to 3.

[0034] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 3, the obtained solid material is washed 3 to 5 times with deionized water; the mass ratio of the solid material described in step 3 to the volume ratio of isopropanol is (10g to 25g): (1L to 2.5L). The other steps are the same as those of specific embodiments 1 to 4.

[0035] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the centrifugal speed in step 3 is 1500 r / min, and the centrifugal time is 10 min; the vacuum drying temperature in step 3 is 60°C to 80°C, and the vacuum drying time is 16h to 24h. The other steps are the same as those in specific embodiments 1 to 5.

[0036] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the epoxy resin in step 4 is E51; the curing agent in step 4 is methyl hexahydrophthalic anhydride; and the accelerator in step 4 is DMP-30. The other steps are the same as those in specific embodiments 1 to 6.

[0037] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that the mass ratio of the epoxy resin, curing agent and accelerator described in step four is 100:80:2; the total mass ratio of BNNS@Fe3O4 to epoxy resin, curing agent and accelerator described in step four is (5g~30g):(70g~95g).

[0038] The other steps are the same as those in Specific Embodiments 1 to 7.

[0039] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the vacuum stirring time in step 4 is 1.5h to 2.5h; the procedure of temperature-raising magnetic curing in step 4 is: heating from room temperature to 80°C, keeping at 80°C for 2h, then heating to 120°C, keeping at 120°C for 2h, finally heating to 160°C, keeping at 160°C for 2h, and then cooling to room temperature; the heating rate is 5°C / min to 10°C / min; the cooling rate is 10°C / min to 15°C / min; the intensity of the magnetic field in step 4 is 0.5T to 1T. The other steps are the same as those in specific embodiments 1 to 8.

[0040] Specific implementation method ten: This implementation method is an application of a vertically oriented boron nitride / epoxy resin thermal conductive composite material in electronic packaging under a magnetic field.

[0041] The following examples are used to verify the beneficial effects of the present invention:

[0042] Embodiment 1: A method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field is specifically completed by the following steps:

[0043] 1. Preparation of a mixed solution of boron nitride and ferroferric oxide:

[0044] Add 10 g of boron nitride and 1 g of ferroferric oxide to 1 L of isopropanol and ultrasonicate for 20 min to obtain a mixed solution of boron nitride and ferroferric oxide;

[0045] The particle size of the boron nitride in step 1 is 25 μm, and the particle size of the ferroferric oxide is 20 nm;

[0046] Second, a mixed solution of boron nitride and ferroferric oxide was circulated and flushed 20 times by a high-pressure homogenizer, and the boron nitride was induced to peel off and physically bond with ferroferric oxide by various fluid dynamics such as shear, turbulence and collision caused by liquid phase flushing, thereby obtaining a boron nitride nanosheet solution with ferroferric oxide attached to the surface;

[0047] The homogenizing pressure of the high-pressure homogenizer described in step 2 is 100 MPa and the working rate is 10 L / h;

[0048] 3. The boron nitride nanosheet solution with ferroferric oxide attached to the surface was vacuum filtered, and the obtained solid matter was washed 5 times with deionized water, and then isopropanol was added, and the supernatant was collected after centrifugation for a period of time, and the collected supernatant was vacuum dried to obtain BNNS@Fe3O4;

[0049] The mass ratio of the solid substance described in step 3 to the volume ratio of isopropanol is 10 g:1 L;

[0050] The centrifugal speed in step 3 is 1500 r / min, and the centrifugal time is 10 min;

[0051] The vacuum drying temperature in step 3 is 60°C and the vacuum drying time is 24h;

[0052] Fourth, BNNS@Fe3O4, epoxy resin, curing agent and accelerator were stirred in a vacuum stirring box for 2 hours to mix evenly to obtain a mixed colloid; the mixed colloid was transferred to a polytetrafluoroethylene disc mold, the mold containing the mixed colloid was placed between two electromagnets, and the temperature was raised and cured under a magnetic field to obtain a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field (the filler addition amount was 5%);

[0053] The epoxy resin described in step 4 is E51;

[0054] The curing agent described in step 4 is methylhexahydrophthalic anhydride (MHHPA);

[0055] The accelerator described in step 4 is DMP-30;

[0056] The mass ratio of the epoxy resin, curing agent and accelerator described in step 4 is 100:80:2;

[0057] The total mass ratio of BNNS@Fe3O4 to epoxy resin, curing agent and accelerator described in step 4 is 5g:95g;

[0058] The procedure of heating and curing in step 4 is: heating from room temperature to 80°C, keeping at 80°C for 2h, then heating to 120°C, keeping at 120°C for 2h, finally heating to 160°C, keeping at 160°C for 2h, and then cooling to room temperature; the heating rate is 5°C / min; the cooling rate is 10°C / min;

[0059] The intensity of the magnetic field described in step 4 is 0.75T.

[0060] Example 2: The difference between this example and Example 1 is that the total mass ratio of BNNS@Fe3O4 to epoxy resin, curing agent and accelerator in step 4 is 10g:90g (the amount of filler added is 10%). The other steps and parameters are the same as those in Example 1.

[0061] Example 3: The difference between this example and Example 1 is that the total mass ratio of BNNS@Fe3O4 to epoxy resin, curing agent and accelerator in step 4 is 20g:80g (the amount of filler added is 20%). The other steps and parameters are the same as those in Example 1.

[0062] Example 4: The difference between this example and Example 1 is that the total mass ratio of BNNS@Fe3O4 to epoxy resin, curing agent and accelerator in step 4 is 30g:70g (the amount of filler added is 30%). The other steps and parameters are the same as those in Example 1.

[0063] Comparative Example 1: The preparation method of the boron nitride / epoxy resin thermal conductive composite material is specifically completed according to the following steps:

[0064] Stirring boron nitride (BN), epoxy resin, curing agent and accelerator in a vacuum stirring box for 2 hours to mix evenly and obtain a mixed colloid; transferring the mixed colloid to a polytetrafluoroethylene disc mold, and heating and curing the mold containing the mixed colloid to obtain a boron nitride / epoxy resin thermal conductive composite material (BN / EP);

[0065] The epoxy resin is E51;

[0066] The curing agent is methylhexahydrophthalic anhydride (MHHPA);

[0067] The accelerator is DMP-30;

[0068] The mass ratio of the epoxy resin, curing agent and accelerator is 100:80:2;

[0069] The total mass ratio of BN to epoxy resin, curing agent and accelerator is 0:100, 5:95, 10:90, 20:80 or 30:70;

[0070] The temperature-raising curing procedure is as follows: heating from room temperature to 80°C, keeping at 80°C for 2 hours, then heating to 120°C, keeping at 120°C for 2 hours, finally heating to 160°C, keeping at 160°C for 2 hours, and then cooling to room temperature; the heating rate is 5°C / min; the cooling rate is 10°C / min.

[0071] Figure 1 This is a picture of the BNNS@Fe3O4 powder prepared in Example 1 dispersed in isopropanol and attracted by a permanent magnet;

[0072] Figure 1 It shows that the BNNS@Fe3O4 powder dispersed in isopropanol is attracted by the permanent magnet, and there is no separation of the two fillers, indicating that the magnetic response characteristics of boron nitride are transformed from non-magnetic to magnetic.

[0073] Figure 2 This is the SEM image of BNNS@Fe3O4 prepared in Example 1;

[0074] from Figure 2It can be seen that the spherical particles of Fe3O4 are distributed on the BNNS, indicating that the liquid phase flushing of the high-pressure homogenizer can successfully bond the Fe3O4 nanoparticles to the surface of BNNS.

[0075] Figure 3 This is a SEM image of a cross section of a vertically oriented boron nitride / epoxy resin thermally conductive composite material prepared in Example 1 under a magnetic field;

[0076] from Figure 3 It can be seen that most of the BNNS@Fe3O4 particles inside the composite material are arranged vertically along the out-of-plane direction.

[0077] Figure 4 It is a comparison diagram of XRD of the vertically oriented boron nitride / epoxy resin thermal conductive composite material prepared under a magnetic field in Example 1 and the boron nitride / epoxy resin thermal conductive composite material prepared without using a magnetic field;

[0078] from Figure 4 It can be seen that after magnetization, the (110) diffraction peak indicating the vertical orientation of boron nitride increases significantly compared with the unmagnetized boron nitride composite material, indicating that the vertical orientation of the filler is successful.

[0079] Thermal conductivity test: The thermal conductivity of the composite materials obtained in Examples 1-4 was tested using an LFA447 laser thermal conductivity tester produced by Netzsch, Germany. The thermal conductivity tested was in the out-of-plane direction perpendicular to the plane of the composite material. Before the test, the sample was prepared into a cylindrical shape with a diameter of 12.7 mm and a thickness of about 1 mm. The upper and lower surfaces of the composite material were ground to be parallel and smooth, and a thin layer of graphite was sprayed on the upper and lower surfaces. The results are shown in Figure 2. Figure 5 As shown, it can be seen that with the increase of BNNS@Fe3O4 filling amount, the out-of-plane thermal conductivity of the epoxy composite material is significantly improved. The thermal conductivity of the BNNSs / EP composite material of Example 4 reaches 1.81W / (m·K), which is 9.05 times that of pure epoxy resin (0.2W / (m·K)).

[0080] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of a mixed solution of boron nitride and ferroferric oxide: Adding boron nitride and ferroferric oxide into isopropanol, and dispersing them evenly under ultrasonic conditions to obtain a mixed solution of boron nitride and ferroferric oxide; 2. Using a high-pressure homogenizer to treat a mixed solution of boron nitride and ferroferric oxide for a period of time to obtain a boron nitride nanosheet solution with ferroferric oxide attached to the surface; 3. The boron nitride nanosheet solution with ferroferric oxide attached to the surface is vacuum filtered, the obtained solid matter is washed, and then isopropanol is added, and the supernatant is collected after centrifugation for a period of time, and the collected supernatant is vacuum dried to obtain BNNS@Fe3O4; 4. BNNS@Fe3O4, epoxy resin, curing agent and accelerator are vacuum stirred for a period of time to mix evenly to obtain a mixed colloid; the mixed colloid is transferred to a polytetrafluoroethylene disc mold, the mold containing the mixed colloid is placed between two electromagnets, and the temperature is increased and cured under a magnetic field to obtain a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field.

2. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The particle size of the boron nitride described in step 1 is 10 μm to 30 μm, and the particle size of the ferrosoferric oxide is 20 nm to 100 nm.

3. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The mass ratio of boron nitride to ferroferric oxide described in step 1 is 5:(0.25-1); the concentration of boron nitride in the mixed solution of boron nitride and ferroferric oxide described in step 1 is 10 mg / mL.

4. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The pressure of the high-pressure homogenizer described in step 2 is 50MPa to 180MPa, the number of cycles is 10 to 30 times, and the working rate is 5L / h to 10L / h.

5. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that In step 3, the obtained solid material is washed 3 to 5 times with deionized water; the volume ratio of the mass of the solid material described in step 3 to isopropanol is (10 g to 25 g): (1 L to 2.5 L).

6. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The centrifugal speed in step 3 is 1500 r / min, and the centrifugal time is 10 min; the vacuum drying temperature in step 3 is 60° C. to 80° C., and the vacuum drying time is 16 h to 24 h.

7. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The epoxy resin described in step 4 is E51; the curing agent described in step 4 is methyl hexahydrophthalic anhydride; and the accelerator described in step 4 is DMP-30.

8. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The mass ratio of the epoxy resin, curing agent and accelerator described in step 4 is 100:80:2; the total mass ratio of BNNS@Fe3O4 to the epoxy resin, curing agent and accelerator described in step 4 is (5g~30g):(70g~95g).

9. The method for preparing a vertically oriented boron nitride / epoxy resin thermally conductive composite material under a magnetic field according to claim 1, characterized in that The vacuum stirring time described in step 4 is 1.5h to 2.5h; the program of heating magnetic curing described in step 4 is: heating from room temperature to 80°C, keeping warm at 80°C for 2h, then heating to 120°C, keeping warm at 120°C for 2h, finally heating to 160°C, keeping warm at 160°C for 2h, and then cooling to room temperature; the heating rate is 5°C / min to 10°C / min; the cooling rate is 10°C / min to 15°C / min; the intensity of the magnetic field described in step 4 is 0.5T to 1T.

10. Application of a vertically oriented boron nitride / epoxy resin thermal conductive composite material under a magnetic field prepared by the preparation method according to claim 1, characterized in that Application of a vertically oriented boron nitride / epoxy resin thermal conductive composite material in electronic packaging under a magnetic field.

Citation Information

Patent Citations

  • Preparing method for polymer composite heat dissipating material

    CN105038136A

  • Oriented arrangement boron nitride high-thermal-conductivity composite material and preparation method thereof

    CN113831685A

  • Heat-conductive insulator sheet, metal based board and circuit board, and manufacturing method thereof

    JP2013254880A

  • Heat conductive particle, composite material, and method for manufacturing the same

    JP2023173930A

  • Heat-conductive film and production method therefor

    US20130309485A1

Cited By

  • Novel battery cell large-area buffer heat insulation pad and preparation method thereof

    CN120082211A

  • Preparation method of aramid nanofiber-based composite film with high thermal conductivity and breakdown resistance

    CN121064510A

  • Preparation method of aramid nanofiber-based composite film with high thermal conductivity and high breakdown resistance

    CN121064510B

  • Dry-type iron core reactor coil resin anti-cracking method

    CN121083831A

  • A method for preventing resin cracking in dry-type iron-core reactor coils

    CN121083831B